The Intergenerational Transmission of Human Capital: Evidence from the Golden Age of Upward Mobility - Card, David; Domnisoru, Ciprian; Taylor, Lowell (Journal of Labor Economics, 2022)
School quality affects upward mobility in educational attainment. This conclusion comes from an analysis of families with coresident teenage children in the 1940 census. We study parents in the bottom quartile of the education distribution and define “upward mobility” as a generational move up the educational ladder to the top three quartiles of the child’s cohort. At the state level, upward mobility is strongly tied to teacher wages. This relationship holds when we narrow our focus to families on adjacent sides of state borders in the South, where state minimum salary laws created sharp teacher-wage differences between otherwise similar counties.